The Impacts of Knowledge Management on Organizational Performance: The Effect of Information Technology - Lau, Cia Wee (Universiti Malaysia Sarawak (UNIMAS), 2019)
This research aims to explore the relationship between knowledge management and organizational performance and how information technology moderates the relationship. Specifically, this study examined the impact of knowledge management on organizational performance around Malaysia. The three dimensions of knowledge management such as knowledge acquisition, knowledge dissemination and responsiveness to knowledge, have been used to study their impact on organizational performance. A total six hypothesis were developed according to the proposed theoretical framework. This study enhances both scholars' and practitioners' understanding on the impact of information technology as a moderator in moderating the relationship between knowledge management and organizational performance.